Firearm possession and violent death: A critical review - Wolfgang Stroebe (Center for Research in Economics, Management and the Arts (CREMA), 2014)
This article critically reviews the empirical research on the association of firearmpossession with suicide and homicide. Both suicide and homicide reflect intentional behavior with the goal of killing oneself or another person. Firearms providemerely a means of reaching this goal. The possession of a firearm can, therefore, not be a primary cause of either suicide or homicide.However, since a defining characteristic of both suicide and homicide is the success of killing, and since guns aremore effective means for reaching this goal than poison or otherweapons, the rate of firearm possession can be expected to be positively related to overall rates of suicide and homicide. This prediction has been tested with individual-level as well as macro-level studies. Individual-level studies, which typically use case–control designs, allow a better control than macro-level studies of the cultural, demographic, and economic determinants of suicide and homicide. In macro-level studies, the potential impact of gun possession on overall rates is likely to be confounded by the factors thatmotivate people to commit suicide or homicide. Despite thesemethodological limitations, the research reviewed in this article supports the assumption that easy access to firearms increases the risk of dying from violent causes. With very few exception, studies found gun ownership positively related to gun-related suicides and homicides. Furthermore, there is evidence that guns do not merely serve as substitutes for other means of killing, but increase the overall rates of suicide and homicide.
Keywords: 330